1988
DOI: 10.1002/j.1460-2075.1988.tb03184.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid turnover of adenovirus E1A is determined through a co-translational mechanism that requires an aminoterminal domain.

Abstract: The product of the adenovirus E1A 13S mRNA can both stimulate and repress the expression of certain viral and cellular genes. As with several other regulatory proteins, E1A has a short half‐life, approximately 40 min. Although this short half‐life is observed in cells expressing the E1A gene, it is not the case with cells injected with E1A protein, where its half‐life is very long, generally greater than 15 h. We have sought to reconcile these apparent differences in E1A stability. Using Xenopus oocytes, we fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
1
1

Year Published

1989
1989
1995
1995

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 39 publications
(36 reference statements)
1
26
1
1
Order By: Relevance
“…The ubiquitin system may recognize abnormal/truncated/misfolded proteins, but not their normal counterparts. For example, a truncated form of E1A adenovirus protein (amino acid residues 1-85) is much more sensitive to degradation then the wild type (1-289) protein (29,43). The case of p53 is even more illustrative, although the direction appears to be "opposite."…”
Section: Resultsmentioning
confidence: 99%
“…The ubiquitin system may recognize abnormal/truncated/misfolded proteins, but not their normal counterparts. For example, a truncated form of E1A adenovirus protein (amino acid residues 1-85) is much more sensitive to degradation then the wild type (1-289) protein (29,43). The case of p53 is even more illustrative, although the direction appears to be "opposite."…”
Section: Resultsmentioning
confidence: 99%
“…The GAL4 fusion proteins are all expressed at equivalent levels (within two-to threefold) in CHO cells (data not shown). 1 amino-terminal sequence, an important determinant of protein stability (Bachmair et al 1986;Slavicek et al 1988); and (2) facilitate specific control experiments. Deletion of the first 19 or 76 amino acids of IE protem results in GAL4-IE derivatives, GAL4-IE (30-1460) and GAL4-IE (77-1460), Mrhich fail to activate E4 transcription.…”
Section: Ie Protein Amino Acids 1-34 Are Critical For Activation Of Pmentioning
confidence: 99%
“…We subsequently showed that the stability of this protein was not merely a function of bacterial expression, since ElA synthesized in a rabbit reticulocyte lysate from an SP6-derived mRNA was also stable in injected oocytes. When ElA was synthesized in oocytes from injected mRNA, however, it exhibited its characteristic short half-life (44). Thus, the half-life of ElA appeared to be related to the translation of its message.…”
mentioning
confidence: 99%
“…amino-terminal region of ElA protein that included the penultimate residue, an arginine, was important for its degradation in mRNA-injected oocytes (44).…”
mentioning
confidence: 99%